Carborane-containing copolyester fibers with unique neutron shielding properties. (15th June 2019) - Wu, Yuane; Hu, Jianjing; Feng, Chen; Chen, Gong; Yang, Jiping
Abstract: Two series of carborane-containing copolyesters were prepared by copolymerization of the newly designed 5-(1-methoxy- o -carborane)dimethyl isophthalate (BDMI) and conventional polyester monomers. Then carborane-containing copolyester fibers were fabricated through melt spinning and the spinning conditions were explored to get the continuous fibers in meters long. The melting point of copolyesters was found to be reduced with the increase of BDMI, indicative of a decrease in spinning temperature. Due to the combination effect of long-chain branch, ether linkage and carborane groups, the glass transition temperature of resulting fibers tended to be decreased first and increased later with the addition of BDMI. Although their tension properties decreased slightly, the resulting fibers also displayed Young's modulus over 3.1 GPa and breaking strength above 66 MPa, while their thermal stabilities were greatly improved by the addition of BDMI. More importantly, the resulting copolyesters possessed outstanding neutron shielding properties. Especially, at a 20% loading level of the carborane-containing monomer BDMI, the resulting polybutylene terephthalate-based copolyester presented the highest neutron absorption cross-section of 17.04 cm −1 . This demonstration may contribute significantly to the development of polymers with neutron shielding properties for various applications, such as environment and body protection materials. Graphical abstract: Unlabelled Image Highlights: New carborane-containing copolyester fibers were produced via melt spinning. Resulting fibers exhibited good mechanical properties and improved thermal stability. The carborane-containing copolyesters possessed excellent neutron shielding performances.